Teacher morale in the secondary schools of the prelature of Tagum, Davao and its relationship to student academic achievement - Demelino, Marietta Panes (1982)
The primary purpose of this study was to find out what is distinct in a teacher that influences student academic achievement. Teacher morale is an important factor considered to be affecting student academic performance.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Teacher morale; Academic achievement